Experimental verification of spallation inventory calculations. (July 2017) - Findlay, D.J.S.; Škoro, G.P.; Burns, G.J.; Ansell, S.
Abstract: Monte Carlo calculations and gamma-ray spectrometry measurements have been made for a highly irradiated tungsten target from a proton-driven spallation neutron source. A comparison of the calculated and measured activities of 60 Co and 172 Lu in the radionuclide inventory shows surprisingly good agreement. Highlights: Experimental measurement of radionuclide activities calculated by Monte Carlo inventory codes. Gamma-ray spectroscopy of proton-driven tungsten spallation target. Measurements made through walls of transport flask.